2006
DOI: 10.1016/j.yhbeh.2005.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal changes related to paternal and alloparental care in common marmosets (Callithrix jacchus)

Abstract: The physiological mechanisms of parental and alloparental care in cooperatively breeding nonhuman primate species such as the common marmoset (Callithrix jacchus) are poorly known. In this study, we examined prolactin and cortisol plasma levels of fathers and older offspring of both sexes, with and without previous experience in infant carrying, around parturition and during infant carrying. Blood samples were collected from fathers and older offspring and prolactin and cortisol were measured by RIA and EIA, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 75 publications
3
33
2
1
Order By: Relevance
“…Together with the strong effect of proactive food sharing on OT, this indicates that OT levels during periods of intense infant-care do not simply result from physical contact, as suggested for prolactin (Mota et al, 2006). Rather, OT may be involved in the motivational regulation of infant-care, which is also consistent with stimulating effects of exogenous OT-administration on maternal (Kendrick et al, 1987;Pedersen et al, 1994) and non-maternal (Bales et al, 2007;Madden and Clutton-Brock, 2011;Saito and Nakamura, 2011) care-taking in mammals.…”
Section: Accepted M Manuscriptmentioning
confidence: 62%
See 1 more Smart Citation
“…Together with the strong effect of proactive food sharing on OT, this indicates that OT levels during periods of intense infant-care do not simply result from physical contact, as suggested for prolactin (Mota et al, 2006). Rather, OT may be involved in the motivational regulation of infant-care, which is also consistent with stimulating effects of exogenous OT-administration on maternal (Kendrick et al, 1987;Pedersen et al, 1994) and non-maternal (Bales et al, 2007;Madden and Clutton-Brock, 2011;Saito and Nakamura, 2011) care-taking in mammals.…”
Section: Accepted M Manuscriptmentioning
confidence: 62%
“…Positive evidence related to non-maternal care exists for example for tamarin fathers, who show changes of testosterone, estradiol, and glucocorticoid levels in the pre-partum period as well as during infant-care, possibly preparing males for the impending birth and parenting role (Ziegler and Snowdon, 2000;Ziegler et al, 2004;Ziegler et al, 1996). Prolactin is also positively linked to infant-care in marmoset fathers and helpers (Dixson and George, 1982;Mota et al, 2006;Mota and Sousa, 2000;Roberts et al, 2001, Schradin andAnzenberger, 2004;Schradin et al, 2003), but these studies suggest that prolactin increases in response to infant-contact and -carrying rather than promoting such behaviors based on motivation-stimulating effects. Accordingly, experienced marmoset fathers could express normal paternal care even if prolactin was suppressed (Almond et al, 2006).…”
mentioning
confidence: 99%
“…Dixson & George [1982] demonstrated that high levels of prolactin were associated with carrying by fathers. Mota et al [2006] and Mota and Sousa [2000] also found that prolactin levels increased after carrying infants in both fathers and older offspring.…”
Section: Introductionmentioning
confidence: 88%
“…Biologists from several fields are increasingly concerned about animal welfare. This is because, as well as the growing importance of ethical issues, the conditions in which animals are maintained may affect results obtained in behavioural, physiological, chronobiological and pharmacological studies, among others [Abbott et al, 2003;Barbosa and Mota, 2004;Mota et al, 2006;Gonçalves et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…They are an important resource in scientific research and are studied in groups [Mota et al, 2006;Barbosa and Mota, 2009] and reproductive pairs [Barbosa and Mota, 2004;Ziegler et al, 2005]. Despite the importance of social interaction for this species, in some studies the animals are kept isolated [Cunha et al, 2006;Chen et al, 2009;Yamaguchi et al, 2010], leading to a negative impact on the health and welfare of these animals.…”
Section: Introductionmentioning
confidence: 99%